Prevalence and Associated Factors of Depression, Anxiety and Stress Among Doctors in North Borneo - Syarifah Nurul Ain; Chua Sze Hung; Aida Nurbaini Arbain; Sarah Marilyn Amin; Teoh Eu Vin; Ferro Firdaus Ibrahim; Loo Jiann Lin (2020)
Introduction: Doctors are known to deal with high occupational stress, causing increased risk of depression, anxiety and stress.Nevertheless, the prevalence and associatedfactors of depression, anxiety and stress among registered doctorsworking in 24 public hospitals in Sabah, Malaysia are not known yet. Methods: This cross-sectional study was conducted using convenient sampling from September-October 2018. The data of 21-item Depression Anxiety Stress Scale (DASS-21) was collected via online link anonymously. Results: Among 314 doctors, majority of them were females (62.1%), mean age 29 (SD 2.72), non-Sabahan (82.8%), Malays (46.8%), not married (78.3%) and medical officers (93.6%). Prevalence of severe/extremely severe anxiety symptoms was 27.4%,depression (22.9%) and stress (18.5%). Doctors perceiving themselves to be depressed, anxious and/or stressed were more likely to develop the corresponding symptoms. Females and Chinese were twice more likely to report anxiety symptoms. Being married had protective effect against depressive symptoms, while working in same hospital for longer time had a significant but weak protective effect against anxiety and stress symptoms. Conclusions: Mental health issue among doctors is substantial and need to be addressed effectively for the benefit of their life, patients and country.